Perancangan Mesin Tetas Telur Otomatis Menggunakan Sensor Suhu dan Sensor Udara - Surapati, Alex; Rinaldi, Reza Satria; Wahyudi, Okta (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2020)
ABSTRACTThe design of quail egg incubators is intended to facilitate the hatching process. The heat source used in the incubator is produced from heaters that use incandescent lamps and humidifiers are used as humidity regulators. The temperature regulator uses a fan to maintain air circulation and reduce the temperature when the temperature has exceeded the setpoint. This tool is equipped with a DHT11 temperature and humidity sensor, an incubator motor is used for the egg turning process, a sound sensor is used to detect if an egg has hatched and a GSM module will send an SMS notification to the farmer. The whole system is controlled by Arduino Mega 2560. During the hatching period, the temperature needed to incubate quail eggs is 39oC and humidity is 60%. The eggs in the hatching machine are rotated once every 3 hours with a 45o rotation angle. This is so that the egg can be heated evenly. The hatching process takes 18 days, with a hatching success rate of 98% of 50 eggs. The use of power in the hatching machine is on average 62.44 watts up to 83.45 watts and for 1 hatching period for 18 days, that is 25.2392kWh.Keywords: Arduino Mega 2560, DHT11, humidifier, GSM module